Pengaruh Manajemen Rantai Pasok Terhadap Daya Saing Dan Kinerja Perusahaan Jasa Konstruksi Perseroan Terbatas Adhi Karya (Persero) Terbuka Medan - Dinda Talya Sari; Retnawati Siregar; Desy Astrid Anindya (Universitas Medan Area, 2022)
The purpose of this study was to determine the effect of supply chain management on the competitiveness and performance of construction service company PT Adhi Karya (Persero) Tbk. This type of research is the associative type, the population in this study is the entire financial report of PT Adhi Karya. The sample in this study is Adhi Karya's 2010-2020 quarterly financial statements. The type of data used in this research is quantitative data. Sources of data used are secondary data sources. The data collected were analyzed by simple linear regression with a test using SPSS 26.0. The results of this study indicate that supply chain management has a positive and significant impact on the competitiveness of the construction service company PT Adhi Karya (Persero) Tbk. This means that if the supply chain value is better for the company, it will increase the competitiveness of Adhi Karya's company, and vice versa, if the company's value or policy in supply chain management is lower, it will reduce the level of competitiveness faced by the company. Supply Chain Management has a positive and significant effect on the performance of the Construction Services company PT Adhi Karya (Persero) Tbk. This means that the better the supply chain management of the company, the better the influence on the company's performance.